The Influence of Instagram on Interest and Purchasing Decisions on Shopee E-Commerce (Case Study of Students in Politeknik Negeri Medan) - Deny Juni Hansen Sembiring; Efni Siregar; Ratna Dewi (CERED Indonesia Institute, 2023)
This research aims to determine and analyze the influence of Instagram on interest and purchasing decisions among Medan State Polytechnic students. This research took research subjects from Medan State Polytechnic students, especially Shopee e-commerce users. The type of research used is quantitative research with survey methods. The subjects in this research were 100 respondents using non-probability sampling techniques and purposive sampling techniques. The research method used was structural equation modeling (SEM), which was processed using the SmartPLS program. The results of this research show that: (1) Instagram has a positive and significant effect on purchasing interest on Shopee among Students of Politeknik Negeri Medan; (2) Instagram has a positive and significant effect on purchasing decisions on Shopee among Students of Politeknik Negeri Medan. (3) Interest buying has a positive and significant effect on purchasing decisions on Shopee among Students of Politeknik Negeri Medan; (4) Instagram has a positive and significant effect on purchasing decisions through the moderator variable buying interest on Shopee among Students of Politeknik Negeri Medan. The variable most dominantly influenced by Instagram is the purchase interest variable.